The use of documentary sources on the internet to verify digital information: case studies - Marcos Recio, Juan Carlos; Edo Bolós, Concha; Parra Valcarce, David (Revista General de Información y Documentación, 2019)
For more than a quarter of a century, newspapers are looking for their place in society. They lost it when the technology became digital and facilitated the way to create, produce and send content. Between digital media and readers, there is no relationship of equality, of necessity, or even of interest in information, because most of them find it on other Internet sites. The technological transformation to which they have been subjected is only the tip of the iceberg they face today. The changes are not only technological, but economic, financial for the environment, social and credibility. The latter is in fashion among the scientific community, for the large number of false content circulating in the networks and also in some newspapers. We must regain confidence in the media. This article aims to evaluate the documentary sources used in digital newspapers to verify information. For this, a study of the Spanish digital media and the use of their social networks is made.